A Case Study of Production Practices and User Participation in an Advertising-Free Digital News Media Organisation - Sreekala Girija (tripleC: Communication, Capitalism & Critique)
The rising adoption of the Internet in India has contributed to the growth of digital news media organisations. Unlike the traditional advertiser-subsidised business model based on audience commodification, some of these new media firms rely on technology to offer news as a public service under an ad-less business model. Using a case study of Newslaundry, this article critically analyses whether interactive online technologies can help create media organisations untainted by the economic rationalities of capitalism. Following a mixed methodology approach that utilises data from 25 interviews with the Newslaundry team and mainstream journalists as well as a variety of text materials, the study finds that news loses its public good character due to Newslaundry’s efforts to make profits. The analysis suggests that the interactive nature of the Internet does not automatically lead to democratic participation.